Internet-delivered cognitive therapy for social anxiety disorder: a development pilot series. - Stott, R; Wild, J; Grey, N; Liness, S; Warnock-Parkes, E; Commins, S; Readings, J; Bremner, G; Woodward, E; Ehlers, A; Clark, D (2013)
BACKGROUND: Randomized controlled trials have established that individual cognitive therapy based on the Clark and Wells (1995) model is an effective treatment for social anxiety disorder that is superior to a range of alternative psychological and pharmacological interventions. Normally the treatment involves up to 14 weekly face-to-face therapy sessions. AIM: To develop an internet based version of the treatment that requires less therapist time. METHOD: An internet-delivered version of cognitive therapy (iCT) for social anxiety disorder is described. The internet-version implements all key features of the face-to-face treatment; including video feedback, attention training, behavioural experiments, and memory focused techniques. Therapist support is via a built-in secure messaging system and by brief telephone calls. A cohort of 11 patients meeting DSM-IV criteria for social anxiety disorder worked through the programme and were assessed at pretreatment and posttreatment. RESULTS: No patients dropped out. Improvements in social anxiety and related process variables were within the range of those observed in randomized controlled trials of face-to-face CT. Nine patients (82%) were classified as treatment responders and seven (64%) achieved remission status. Therapist time per patient was only 20% of that in face-to-face CT. CONCLUSIONS: iCT shows promise as a way of reducing therapist time without compromising efficacy. Further evaluation of iCT is ongoing.